Around the world in 10 million years: Rapid dispersal of a kleptoparasitoid spider wasp (Pompilidae: Ceropales). (2nd April 2021) - Rodriguez, Juanita; Bank, Sarah; Waichert, Cecilia; von Dohlen, Carol D.; Pitts, James P.
ABSTRACT: Aim: Cosmopolitan distributions have classically been explained by Pangaean vicariance. However, evidence of recently diverged cosmopolitan groups has re‐opened consideration on the processes involved. Our aim is to estimate the processes leading to the worldwide distribution of the kleptoparasitoid genus Ceropales . Location: Worldwide. Taxon: Ceropales spider wasps (Pompilidae). Methods: Data from three molecular markers for 52 specimens of Ceropales and two calibration points from previous analyses were used to reconstruct a dated phylogeny under a relaxed molecular clock. We compared the fit of 12 models using BioGeoBEARS: DEC (subset sympatry, narrow vicariance), DIVALIKE (narrow and wide vicariance), BAYAREALIKE (widespread sympatry), and these same models with an added jump dispersal parameter and constraining dispersal rates among areas. Using the AIC best‐fit model (DEC+J), we performed Biogeographic Stochastic Mapping (BSM) to infer biogeographic processes by simulating 200 BSM on the BEAST chronogram. Results: The origin of crown‐group Ceropales was ca. 10.6 Ma (15.7–6.5 95% HPD), and 11 jump‐dispersal events explain its distribution. A constrained DEC+J model, allowing adjacent area dispersal was the best‐fit AIC model. Dispersals across the Bering land bridge, Isthmus of Panama, Mediterranean Sea, and Sunda Plains took place from the late Miocene to present times. Main conclusions: Ceropales is a recently diverged group that originated in Eurasia in the Miocene and dispersed to occupy the Americas, Africa, and Australia. Colonization was probably favored by the already diversified hosts (Pompilinae and Pepsinae), which reduced limiting factors such as food resource and nest construction. The evolution of a generalist parasitic lifestyle could facilitate long‐distance dispersal. This is the first study addressing the global historical biogeography of a cosmopolitan spider wasp.